Effects of oral tauroursodeoxycholic acid and/or intestinal probiotics on serum biochemical indexes and bile composition in patients with cholecystolithiasis - Gao, Fan; Guan, Dongyao; Wang, Gangliang; Zhang, Luting; He, Junmin; Lv, Wenqiao; Zhang, Xiaofeng; Tao, Weifeng; Dai, YeFeng; Xu, Song; Chen, Yeqi; Lu, Bin (Frontiers in Pharmacology, 2022)
Background:It is well known that the hepatoenteric axis plays a key role in gallstone formation,and it is gradually becoming a research focus.Cholesterol homeostasis can be regulated by the liver and intestinal tract in our bodies,and intestinal flora can regulate the digestion and absorption of cholesterol.These two factors are closely related to the formation of gallstones.Aim:To investigate the effects of tauroursodeoxycholic acid(TUDCA) and/or intestinal probiotics on serum biochemical indexes and bile composition in patients with cholecystolithiasis.Methods:For this study,96 patients with cholecystolithiasis were recruited at our hospital.The patients were randomly divided into four groups according to a random number table:groupⅠ(TUDCA,24 cases),groupⅡ(intestinal probiotics,24 cases),group Ⅲ(TUDCA and intestinal probiotics,24 cases) and group Ⅳ(control group, 24 cases).All patients underwent laparoscopic gallbladder-preserving lithotomy or laparoscopic cholecystectomy.Bile samples were identified and extracted during the operation.Results:The results revealed that the levels of serum total bile acid(TBA),serum total cholesterol(TCHOL) and serum triglyceride in groups I, II and III before and after the intervention were statistically significant(P<0.05).There were significant differences in serum low-density lipoprotein cholesterol(LDL-C) between groups I and II before and after the intervention (P<0.05),but the serum LDL-C level in group Ⅲ before and after the intervention was similar(P>0.05).Regarding bile,TBA levels demonstrated no significant difference between groups I and III(P>0.05),and the differences between the other two groups were statistically significant (P<0.05).No significant difference was identified in phospholipid and TCHOL levels between groups I and Ⅲ(P>0.05),and the differences between the other two groups were statistically significant (P<0.05).There were significant differences in the levels of free Ca2+,pH value and glycoprotein in bile among the four groups(P<0.05).The levels of cholic acid,chenodeoxycholic acid and deoxycholic acid in bile were significantly different among the four groups(P<0.05).The level of lithocholic acid(LCA) in groups Ⅱ and Ⅲ was similar, as was the level of LCA in groups I and ⅠV,but difference in level between the other two groups was statistically significant(P<0.05).Conclusion:The combination of TUDCA and intestinal probiotics did not enhance the effect of either treatment.Use of intestinal probiotics alone can maximise the reverse development of bile composition in patients with cholecystolithiasis compared with TUDCA alone and a combination of TUDCA and intestinal probiotics,thereby reducing gallstone formation.